Intensification of adsorptive ceramic ultrafiltration membrane system by nanoclay coating and multivariate optimization of humic acid removal - Al-Mutwalli, Sama A.; Taher, Mustafa N.; Yokus, Senem; Can-Guven, Emine; Guvenc, Senem Yazici; Koseoglu-Imer, Derya Y.; Varank, Gamze (ELSEVIER, 2024)
In this study, humic acid (HA) removal was investigated by a ceramic ultrafiltration membrane coated with nanoclay (NC). First, the adsorption capacity of NC was determined, and isotherm, kinetic, and thermodynamic studies were conducted. Second, the HA removal efficiency of the NC-coated ceramic ultrafiltration membrane was determined. Box-Behnken Design, one of the response surface methodologies, was applied to optimize the operating parameters of the membrane process and develop a mathematical model, and analysis of variance (ANOVA) was performed to determine the interaction between the process variables and the system responses (membrane flux and HA removal). The optimum process parameters at which maximum HA removal efficiency was achieved were as follows: HA initial concentration: 20.9 mg/L, initial pH: 3, temperature: 45.9 degrees C. Under optimum conditions, the estimated HA removal efficiency was 70.6 % and it was 68.1 % in the validation experiments, which were conducted to check the model. The results of the study show that it is possible to remove high amounts of humic content from the leachate NF concentrate by NC-coated ceramic membrane filtration.
Keywords: Box-Behnken design; Ceramic membrane; Humic acid removal; Nanoclay; LEACHATE NANOFILTRATION CONCENTRATE; RESPONSE-SURFACE METHODOLOGY; LANDFILL LEACHATE; FENTON OXIDATION; SUBSTANCES; DESIGN; BIODEGRADABILITY; DEGRADATION; FILTRATION; Engineering; Water Resources